A New Multi-Domain Hybrid Microgrid Design Integrating Reliability and Stability Simultaneously - Ali Azizi; Saeed Peyghami; Frede Blaabjerg (IEEE Access)
Dynamic failures within hybrid microgrids are often initiated from stability issues, substantially elevating the system’s overall risk alongside static failures. The imposition of short and long-term stability constraints frequently necessitates load shedding to ensure stable and reliable hybrid microgrid operation. This work introduces a new and comprehensive multi-domain design guideline that intricately incorporates stability risk with conventional reliability models. It introduces an optimal system design, spanning from component-level to system-level, aimed at sustaining the overall risk within standardized bounds. Initially, time-domain simulations are conducted to determine transient angle stability criteria, serving as pivotal stability constraints for dynamic performance of the hybrid microgrid. Then, utilizing the proposed risk-based design guideline, an exploration into various stability issues impact on system risk is undertaken, revealing their profound influence. The findings clarify that both during the planning and operational phases, the proposed methodology effectively include dynamic and static risks. This improvement is attained by appropriately selecting components at the component-level, optimal sizing of critical equipment concerning quantity and capacity, and the integration of appropriate renewable energy sources. Ultimately, the redesigned structure of the hybrid microgrid guarantees operations within predefined standard risk levels, affirming the effectiveness of the proposed methodology in mitigating risks and ensuring robust system performance in diverse operational scenarios for hybrid microgrids.